Special delEVery: Extracellular Vesicles as Promising Delivery Platform to the Brain - Marie J. Pauwels (MDPI AG, 2021)
The treatment of central nervous system (CNS) pathologies is severely hampered by the presence of tightly regulated CNS barriers that restrict drug delivery to the brain. An increasing amount of data suggests that extracellular vesicles (EVs), i.e., membrane derived vesicles that inherently protect and transfer biological cargoes between cells, naturally cross the CNS barriers. Moreover, EVs can be engineered with targeting ligands to obtain enriched tissue targeting and delivery capacities. In this review, we provide a detailed overview of the literature describing a natural and engineered CNS targeting and therapeutic efficiency of different cell type derived EVs. Hereby, we specifically focus on peripheral administration routes in a broad range of CNS diseases. Furthermore, we underline the potential of research aimed at elucidating the vesicular transport mechanisms across the different CNS barriers. Finally, we elaborate on the practical considerations towards the application of EVs as a brain drug delivery system.